Penguatan Kompetensi Editor dan Desk Reviewer melalui Workshop Kaidah dan Strategi Desk Evaluation untuk Meningkatkan Mutu Pengelolaan Jurnal Ilmiah - Andriyani Andriyani (CV. Doki Course and Training, 2026)
The quality of scientific publications is greatly influenced by the quality of the editorial process, particularly the desk evaluation stage, which serves as an initial screening before articles enter the peer review process. In practice, many journal editors and reviewers still lack a uniform understanding of article assessment indicators according to international journal standards. This condition impacts the less than optimal manuscript selection process and the quality of published articles. This community service activity aims to improve the competence of editors and reviewers through a workshop entitled